The first Ordovician cyclocystoid (Echinodermata) from Gondwana and its morphology, paleoecology, taphonomy, and paleogeography. (9th May 2017) - Reich, Mike; Sprinkle, James; Lefebvre, Bertrand; Rössner, Gertrud E.; Zamora, Samuel
Abstract: Moroccodiscus smithi represents a new cyclocystoid genus and species based on moldic specimens from the Middle Ordovician Taddrist Formation (Darriwilian) of SE Morocco. This represents the earliest articulated member of the Cyclocystoidea and is the first complete cyclocystoid described from the Ordovician of Gondwana, as well as the first cyclocystoid ever recorded from Africa. The anatomy and morphology of this new species were studied using a combination of conventional paleontological methods and nondestructive X-ray computed tomography. Because Moroccodiscus differs from other cyclocystoids, in particular by lacking cupules attached to the marginal ossicles, it is assigned to the new family Moroccodiscidae. This new taxon illustrates the relatively poorly known early diversification of these enigmatic extinct echinoderms and sheds light on the mode of life of cyclocystoids, including injuries to plate circlets during early ontogeny and folding of these disk-like specimens at the time of death. The overall thecal shape was very similar in cyclocystoids and many domal edrioasteroids, probably because they were both sessile or attached, benthic, suspension feeders. However, many oral surface, ambulacral, and marginal ring features had become very different, indicating that these two groups had either converged because of similar life modes or were only distantly related sister groups.